2008
DOI: 10.1021/ma800857d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Linear-Dendron-like Poly(ε-caprolactone)-b-poly(ethylene oxide) Copolymers via the Combination of Ring-Opening Polymerization and Click Chemistry

Abstract: A new class of linear-dendron-like poly(ε-caprolactone)-b-poly(ethylene oxide) (PCL-b-PEO) copolymers with unsymmetrical topology was synthesized via controlled ring-opening polymerization (ROP) of ε-caprolactone (CL) followed by a click conjugation with azide-terminated PEO (PEO-N 3 ). The dendron-like PCL terminated with a clickable alkyne group (Dm-PCL, m ) 0, 1, 2, and 3) was for the first time synthesized from the ROP of CL monomer using a propargyl focal point dendrons Dm with primary amine groups as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
121
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(124 citation statements)
references
References 52 publications
2
121
0
Order By: Relevance
“…38 Preparation of Propargyl-PAMAM Dendrons. In this study, propargyl-PAMAM dendrons were synthesized according to the procedure reported by Lee and Dong et al 39,40 The experimental details were shown in Supporting Information. The chemical structure of propargyl-PAMAM dendron G3.5 was confirmed by 1 H NMR spectra and mass spectra.…”
Section: ' Materials and Methodsmentioning
confidence: 99%
“…38 Preparation of Propargyl-PAMAM Dendrons. In this study, propargyl-PAMAM dendrons were synthesized according to the procedure reported by Lee and Dong et al 39,40 The experimental details were shown in Supporting Information. The chemical structure of propargyl-PAMAM dendron G3.5 was confirmed by 1 H NMR spectra and mass spectra.…”
Section: ' Materials and Methodsmentioning
confidence: 99%
“…[2] TBA was prepared by sequential alkylation and hydrolysis reactions as described elsewhere. [12] The obtained TTBs and TBA were characterized by 1 H and 13 C NMR spectroscopy, elemental analysis, and gel permeation chromatography (GPC).…”
mentioning
confidence: 99%
“…1.11f). Techniques to synthesise these types of materials include the ring opening polymerisation (ROP) of ε-caprolactone initiated from the dendron (PAMAM) periphery, followed by Cu catalysed azide-alkyne 'click' (CuAAC) reaction of a 18 1 Introduction PEG to the focal point [98]. The material properties, such as crystallisation properties and self-assembly in micelles or vesicles, were investigated.…”
Section: Dendritic Hybrid Architecturesmentioning
confidence: 99%